Does intervening to enhance parental involvement in education lead to better academic results for children? An extended review. Issue 3 (21st September 2015) - Tracey Bywater, Dr; See, Beng Huat; Gorard, Stephen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to summarise the results of a review of the literature linking parental involvement in their child's education to attainment at or before primary school. Design/methodology/approach – The search involved nine electronic databases supplemented by other sources, and yielded 4, 898 apparently relevant reports. Of these, 127 were reports of attempted evaluations to see whether enhancing parental involvement led to higher attainment outcomes for children. Findings – None of these studies was a large, robust evaluation. The overwhelming majority (121/127) reported research with serious limitations, and they were almost equally divided between those claiming success and those saying that the intervention had been ineffective or harmful. Of the remaining six, three offered positive outcomes, and these were generally complex interventions in which parental involvement was only part of a package of measures taken to improve results. Originality/value – Therefore, the paper has three main messages for an area where practice and policy interventions abound. Research has to improve greatly.